In vitro and in vivo evaluation of antitumor activity of methanolic extract of Argyreia nervosa leaves on Ehrlich ascites carcinoma - Sharma, Bhawna; Dhamija, Isha; Kumar, Sandeep; Chaudhary, Hema (Bangladesh Journal of Pharmacology, 2015)
The herb of importance like Argyreia nervosa has shown wide range of pharmacological activities. Its methanolic extract of A. nervosa has been explored against Ehrlich ascites carcinoma (EAC) induced liquid and solid tumor in mice. Liquid and solid tumors were induced by intraperitoneal and subcutaneous transplantation of EAC cells in Balb/C mice. Significant and dose dependant results are observed when the mice are sacrificed on 15th day for estimation of tumor proliferation, hematological, biochemical and hepatic antioxidant parameters. Mean survival time (days) was increased to 36.5 from 20.5 extract treated mice. The extract also showed a decrease (p<0.001) in body weight and percentage reduction in tumor volume respectively when it was evaluated in solid tumor induced mice for a period of 30 days. From the result it was concluded that the extract has as a potent antitumor activity and that is comparable to 5-fluorouracil.